2008
DOI: 10.2967/jnumed.108.055046
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Diagnosis of Clinically Suspected Recurrence of Cervical Cancer: Impact of 18F-FDG PET

Abstract: Clarifying the diagnosis of clinically suspected recurrence of cervical cancer can be challenging. The aim of this study was to investigate the clinical value of 18 F-FDG PET in this context. Methods: The medical records of a cohort of 40 18 F-FDG PET referrals in whom recurrence of cervical cancer was clinically suspected were reviewed. Two expert gynecologic oncologists assessed the level of pre-PET clinical doubt, quality of pre-PET work-up, and impact of 18 F-FDG PET on diagnostic understanding and managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 26 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…The large range of PPVs was related to a study investigating the use of FDG-PET for detecting early recurrence in patients without clinical evidence of recurrence, a setting in which one could postulate that a higher false-positive rate might be expected. In the study by Van der Veldt et al, 38 the sensitivity Figure 2 A 66-year-old woman with high-grade müllerian cervical adenocarcinoma, initially treated with chemotherapy and radiation. FDG-PET/CT for the subsequent treatment strategy revealed multiple bilateral FDG-avid pulmonary nodules.…”
Section: Initial Staging-distant Metastatic Evaluationmentioning
confidence: 98%
See 1 more Smart Citation
“…The large range of PPVs was related to a study investigating the use of FDG-PET for detecting early recurrence in patients without clinical evidence of recurrence, a setting in which one could postulate that a higher false-positive rate might be expected. In the study by Van der Veldt et al, 38 the sensitivity Figure 2 A 66-year-old woman with high-grade müllerian cervical adenocarcinoma, initially treated with chemotherapy and radiation. FDG-PET/CT for the subsequent treatment strategy revealed multiple bilateral FDG-avid pulmonary nodules.…”
Section: Initial Staging-distant Metastatic Evaluationmentioning
confidence: 98%
“…37 Conversely, metabolism is usually higher in recurrent malignancy than in posttreatment scarring, and FDG-PET and PET/CT have been shown to be effective in detecting recurrent tumor. [38][39][40][41] The results of several of these studies are summarized in Table 2. The studies included different patient populations and a meta-analysis as well as different techniques (FDG-PET alone vs PET/CT).…”
Section: Initial Staging-distant Metastatic Evaluationmentioning
confidence: 99%
“…PET has a high positive predictive value and is recommended in all cases of recurrent cervical cancer [5]. The recurrence should be proved by a biopsy in all cases [6].…”
Section: Evaluation Of Recurrent Diseasementioning
confidence: 99%
“…In disease re-staging, conventional CECT and MRI are the most frequently used imaging modalities, even if some limitations should be taken into account: first of all, they are generally limited to one body district (pelvis and/or abdomen); secondly, they are often unable to identify cancer relapse in body districts which present post-surgical or post-radiotherapy scars (good sensitivity, but low specificity levels); thirdly, they are inaccurate in characterizing small lymph nodes and in detecting the peritoneal disease [52]. Therefore, as described by van der Weldt [53] the results of the above-mentioned exams are often inconclusive and equivocal, thus justifying the use of PET. In this study the 18 F-FDG-PET/CT scan showed a good sensitivity and specificity: 92% and 93% respectively.…”
Section: Re-stagingmentioning
confidence: 99%